Intersetorialidade no atendimento de crianças e adolescentes usuários de substâncias psicoativas no município de Cascavel-Pr - Tozo, Giancarlo (2019)
This research discusses the intersectoral theme, relating it to public policies with actions focused on drugs, mental health and youth. Several institutions that formulate public policies defend the need of intersectoral articulation to overcome problems related to health. Based on this understanding, some brazilian municipalities seek intersectoral forms of organization and management of public services aimed at vulnerable groups of the population to overcome sectoral fragmentation. Since 2010, the municipality of Cascavel, Paraná, has articulated the Network of Attention and Social Protection - REDE, an intersectoral experience that is under construction. In this sense, the general objective is to understand the relationship and articulation of the Psychosocial Attention Network - RAPS, regarding the care of children and adolescents psychoactive substances’ users with the REDE, in the city of Cascavel - PR. The specific objectives include describing, through historical rescue, the construction of the REDE in the municipality of Cascavel-Pr; identify and describe the channels of communication, flows and other instruments used in the relationship and articulation of the various points of these networks; and to apprehend the vision of the professionals that compose the REDE as representatives on its implementation and weaknesses. For that, a qualitative, descriptive and exploratory research was carried out, through semi-structured interviews with workers that attend young drug users of the services that make up the two networks, from January to April, 2018; and documentary data collection, from June to December 2018, after approval of the human research ethics committee. The data were analyzed using the technique of content analysis, guided by historical materialism. It was possible to observe that attention to the child and adolescent, users of psychoactive substances in the municipality of Cascavel, Paraná, develops with intersectoral network characteristics, with the construction of intersectoral instruments, and can be understood as a collective work process. The interviewees evaluated positively the way the REDE established itself, but they pointed out weaknesses in its effectiveness, mentioning difficulties related to issues such as infrastructure, high demand for services, insufficient human resources, inadequate flow and lack of services to integrate the rede. It is considered that the intersectoral experience of the municipality is under construction, requiring additional studies on its development, which may contribute with reflections on services, and collaborate to broaden policies aimed at the care of children and adolescents psychoactive substances’ users.